Essen and the Ruhr Area: The development of tourism and the role of small firms and entrepreneurs - Lutz Trettin; Uwe Neumann; Guido Zakrzewski (European Regional Science Association (ERSA), 2010)
The city of Essen is located at the centre of the Ruhr area, one of the largest urban and industrial agglomerations in Europe. Like many places in the German federal state of North Rhine-Westphalia Essen had to deal with tremendous structural changes due to the downturn of coal mining and the steel industry since the 1960s. Nevertheless, in the meanwhile the city succeeded in creating a comparatively favourable starting position as an important centre for services, culture and new forms of tourism. Traditionally the headquarters of some of the largest German public companies are located here. Furthermore, the city has become an internationally renowned place of commercial fairs, conferences, and has a university. Essen hosts internationally acknowledged cultural institutions. And recently the building complex of the coal mine "Zollverein" became enlisted by the UNESCO as a World Heritage Memorial. In May 2006 the Ruhr area with Essen as its leading city was finally nominated as European Capital of Culture 2010. Taking all these factors together, a boost of the local tourism sector can be expected. In this context we discuss how the cities economy can gain from this development in the long run. We are interested in the related approaches of the tourism policy and the role of small firms and entrepreneurs in the process of developing a sustainable tourism infrastructure. It is of particular interest how public initiatives of tourism promotion and entrepreneurship support will be combined with the aim to use "industrial heritage tourism" and "cultural tourism" as a mode to economically revive the old industrialized Ruhr area. Thus, central questions of the papers are: Which policy strategies and support measures are appropriate in order to compete with success as an old industrialized area in the field of city and cultural tourism? Who tends to govern the newly establishing value chains? What position remains factual for local young firms therein? What role can public institutions play in order to ensure a high degree of value addition by local economic actors?
Keywords: 330